The high temperature tribological behavior of an iron oxide strengthened iron compound obtained from an industrial byproduct (2022)
This new material is based on an oxide dispersion strengthened iron, obtained by a partial chemical reduction of ground mill scale for subsequent compaction and sintering. The mechanical properties depend on the porosity level and the quantity of the iron oxide reinforcement. Having into account the characteristics of the reinforcement, the tribological behavior was evaluated at two types or ironox compounds under dry sliding conditions. The effect of porosity was evaluated and a comparison with an AISI 1040 steel was done. Experimental test was carried out using a pin on disk tribometer at different temperature. It was found that, on the contrary of AISI 1040 steel, the wear rate of ironox compounds with temperature tends to slow down.